8z-51z+15-30z-15z+2z=53z+15+31z+2z-172

Simple and best practice solution for 8z-51z+15-30z-15z+2z=53z+15+31z+2z-172 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8z-51z+15-30z-15z+2z=53z+15+31z+2z-172 equation:


Simplifying
8z + -51z + 15 + -30z + -15z + 2z = 53z + 15 + 31z + 2z + -172

Reorder the terms:
15 + 8z + -51z + -30z + -15z + 2z = 53z + 15 + 31z + 2z + -172

Combine like terms: 8z + -51z = -43z
15 + -43z + -30z + -15z + 2z = 53z + 15 + 31z + 2z + -172

Combine like terms: -43z + -30z = -73z
15 + -73z + -15z + 2z = 53z + 15 + 31z + 2z + -172

Combine like terms: -73z + -15z = -88z
15 + -88z + 2z = 53z + 15 + 31z + 2z + -172

Combine like terms: -88z + 2z = -86z
15 + -86z = 53z + 15 + 31z + 2z + -172

Reorder the terms:
15 + -86z = 15 + -172 + 53z + 31z + 2z

Combine like terms: 15 + -172 = -157
15 + -86z = -157 + 53z + 31z + 2z

Combine like terms: 53z + 31z = 84z
15 + -86z = -157 + 84z + 2z

Combine like terms: 84z + 2z = 86z
15 + -86z = -157 + 86z

Solving
15 + -86z = -157 + 86z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-86z' to each side of the equation.
15 + -86z + -86z = -157 + 86z + -86z

Combine like terms: -86z + -86z = -172z
15 + -172z = -157 + 86z + -86z

Combine like terms: 86z + -86z = 0
15 + -172z = -157 + 0
15 + -172z = -157

Add '-15' to each side of the equation.
15 + -15 + -172z = -157 + -15

Combine like terms: 15 + -15 = 0
0 + -172z = -157 + -15
-172z = -157 + -15

Combine like terms: -157 + -15 = -172
-172z = -172

Divide each side by '-172'.
z = 1

Simplifying
z = 1

See similar equations:

| -10x-7x=10x+24 | | 5x-13x= | | -4.9t^2+179t+12.4=0 | | (1/3)9s | | 5/5*1/2 | | 20*x-3*y= | | 37+x=2(8+x) | | 5(t-3)+7t=6(2t+5)-8 | | 39=6x+3 | | -5+8=m-4 | | p=6x+3 | | 15t+(4-t)10=50 | | J(x)=x-6 | | y-0.6x=-2 | | z/7=4z/35+2 | | z/7=4z/35z+2 | | 4y-5y+13-3y=9-3y-12y+8y | | 180=x+(3x+12)+y | | e^2x+3=200 | | 41=-12y+5 | | x=-12(1)+5 | | 26-6x=18+2x | | 7x+15=3x+55 | | 51+0.13x=38 | | x=-12(-1)+5 | | 3e^2x+2=50 | | 51+0.13x=38+0.18x | | 8(x-4)=-4x+76 | | -4(5+1)= | | 16x-11=7x+70 | | 4w=3 | | 16x-11=7+70 |

Equations solver categories